A comparison of first trimester blood pressures obtained at the time of first trimester pre-eclampsia screening and those obtained during prenatal care visits. (May 2020) - Seravalli, Viola; Miller, Jena L.; Blitzer, Miriam G.; Baschat, Ahmet A.
Abstract: Objective: To determine if enrollment blood pressures in a study on first trimester preeclampsia prediction significantly differed from those obtained during routine prenatal care visits in the first trimester. Study Design: Women carrying a singleton gestation were prospectively enrolled in a first trimester study on preeclampsia prediction, and had systolic and diastolic blood pressure (SBP, DBP) measured at the time of enrollment. Blood pressure was also measured with the same technique by clinic nurses during the routine prenatal visits throughout the first trimester of pregnancy (9–14 weeks). The enrollment-BP (E-BP) and average first trimester-BP (aFT-BP) were compared using a paired samples t -test or Wilcoxon test, as appropriate. Smokers and patients on antihypertensive medications were excluded from the analysis. test. Results: 644 women had prenatal care in the primary study center and met study criteria. The mean gestational age at study enrollment was 12.5 weeks. No significant difference was found between E-SBP and aFT-SBP (p = 0.10). Enrollment DBP and mean arterial pressure (MAP) were significantly lower than the aFT- DBP and -MAP (median DPB 67 vs 70 mm Hg and median MAP 83.7 vs 85 mmHg, respectively, p < 0.001). However, the difference was not clinically relevant (3 mmHg for DBP, and 1.3 mmHg for MAP). Conclusions: Blood pressures obtained in a setting of preeclampsia screening are not higher than those obtained during regular prenatal care in the first trimester. This suggests that the setting in which pre-eclampsia screening is performed is unlikely to be a confounder for blood pressure measurements and the risk assessment.